Establishment of the emergency material reserve mechanism for public health emergencies and optimization of the management of various functional departments - Sun, Yumeng (Frontiers in Public Health, 2023)
A public health emergency refers to an event that occurs suddenly, causes or may cause serious social harm, and may be caused by a variety of factors. This paper have discussed how to built the reserve mechanism of emergency disposal materials and the best management mode of each functional department in public health emergencies. This paper have proposed a comprehensive evaluation of emergency response capability based on analytic hierarchy process. Based on this study, the optimization experiment results of public health emergency response and management of various functional departments have been analyzed. The results of this experiment have showed that the project implementation rate of the Municipal Center for Disease Control and Prevention was 59.3%, and the average completion rate of the inspection items carried out by the district and county health supervision institutions was 45.8%. According to the characteristics and needs of each region, the project completion rate of the CDC in the city was 20.3%, and the project implementation rate of the district and county health and health administrative departments was 14.8%. In this regard, the training of relevant personnel should be strengthened and run through the whole material reserve work. At the same time, a regular emergency material reserve system was established. According to actual needs, sufficient emergency disposal materials were provided to ensure their normal supply.